Upaya Meningkatkan Hasil Belajar Matematika melalui Metode Kooperatif Tipe Team Accelarated Intruction (TAI) - Ulyati Ulyati (Universitas Indraprasta PGRI, 2018)
This research was conducted after researchers having a problem in teaching mathematics at 10 grade CMS YASPIH RAJEG, kecamatan Rajeg, district of Tangerang. Based on that problem, researchers try to solve those problems by using cooperative learning methode to enhancement student’s mathematics learning achievement. On the classroom action research, subjects are the students of class 10 AP SMK YASPIH RAJEG Rajeg subdistrict of Tangerang Regency consisting of 34 students. This research was conducted at academic years 2012/2013 from January until February 2013. The research results showed that these Class Actions that used cooperative learning methods in cycle I, II and III enhancement learning results. It can be showed from evaluation and observation in cycles I, II dan III, there are some improvements in cycle 1, average completeness only 62 and completeteness level 14.71% (5 students), in cycle II, it increase to 66.17 with completeteness level 52.96% ( 18 students), in cycles III it become 80.13 with completeteness level 91.19% (31 students). It showed that cooperative learning methode can improve student’s learning achievement in mathematics at tenth grade in SMK YASPIH RAJEG